Clinical Dilemma and the Role of Cone-Beam Computed Tomography in the Diagnosis of an Unusual Presentation of Central Odontogenic Tumor—A Case Report - Surenthar, Mouttoukichenin; Srinivasan, Subramanian Vasudevan; Jimsha, Vannathan Kumaran; Vineeth, Ramanathan (Indian Journal of Radiology and Imaging, 2021)
Cone beam computed tomography (CBCT) provides a detailed analysis of the dentition and of cortical and medullary bone free of superimposition inherent in radiographs, which are effortlessly plausible, easily available, and relatively inexpensive when compared with other cross-sectional imaging modalities such as computed tomography (CT) and magnetic resonance imaging (MRI). This article presents a case report of a 23-year-old male patient with a complaint of a mass in the right side lower back tooth region for the past 2 and a half months, which had the unusual presentation of prominent exophytic growth masking the central odontogenic tumor, wherein the diagnostic performances of CBCT in unveiling the diagnostic challenge that led to the clinical dilemma is emphasized. Routine radiographs such as orthopantomogram, mandibular occlusal view were taken along with CBCT, which accentuated the precise diagnosis in this case. The lesion was surgically enucleated with curettage and extraction of the involved teeth. CBCT unveiled the classic multilocularity of ameloblastoma, which routine imaging failed to display. CBCT played a pivotal role in counteracting the diagnostic challenges faced and also in distinguishing it from a cystic lesion that was initially deceived by routine two-dimensional radiographs.
Keywords: ameloblastoma; cone beam computed tomography; exophytic; plexiform